Karakteristik Ungkapan Makian dalam Podcast Akun Youtube Deddy Corbuzier - Kamala, Lailatul; Agustina, Agustina (Universitas Negeri Padang, 2024)
This research examines the use of profanity in Deddy Corbuzier's YouTube podcasts in Indonesia. The study aims to analyze the structure, types, and purposes of cuss words used. Employing a qualitative approach with descriptive methodology, data was collected through observation and recording of words, phrases, and clauses containing profanity. The analysis revealed 95 instances of cuss words, with word form being the most common structure (77 instances). Five categories were identified: conditional, animal-related, object-related, body part-related, and profession-related, with conditional being the most frequent (46 instances). Four functions of cuss word usage were observed: conformity to group norms, insults, expressions of shock or threats, and articulation of intense emotions, with the latter being most prominent (33 instances). Cuss words in these podcasts primarily take the form of single words and serve to describe negative qualities or express emotions, particularly surprise. Notably, they are used for both negative and positive purposes, including humor, to enhance entertainment value in Corbuzier's infotainment-focused podcasts.